Video Gaming Faith: Playing Out Theologies of Religions - Jones, Gregory D. (Religions, 2022)
Modern religious plurality invites religious and non-religious people to navigate four interreligious dialogical problems: (1) the inability to fully articulate faith, (2) the lack of persuasive religious language, (3) the reality of violence among the religions, and (4) the liquescent “truth” of modern times. How can plurality be framed for people whose sense of relationality is shaped by their participation in virtual worlds? One answer emerges in this autoethnographic consideration of how video gaming “plays out” fresh understandings of the interreligious encounter and relationality. Adopting a Christian perspective, the first section summarizes the major theologies of religions. These theologies correspond with video-game experiences of interreligious cooperation and contest found in playing out the enrichment and diminishment of (1) Christian spirit in Spiritual Warfare (NES), (2) human connection in Final Fantasy VI (Super NES), (3) sense of salvation in Final Fantasy X (PS2), and (4) symbiotic sacredness in Journey (iOS). These play experiences clarify a concept of expansive relationality among religions that is termed shared contest. The conclusion advances a contestant theology of religions; God removes every obstacle to including all in the company of God’s people, and God provides a playground of cooperation and contest for each religious tradition.